2020
DOI: 10.1103/physrevresearch.2.032070
|View full text |Cite
|
Sign up to set email alerts
|

Hints for the nematic pseudogap in the nearly optimally doped La2xSrxCuO4 superconductor

Abstract: The in-plane anisotropy of the Seebeck (S) and Nernst (ν) coefficients of the nearly optimally doped cuprate superconductor La 1.86 Sr 0.14 CuO 4 was measured under uniaxial pressure. Regardless of the qualitative differences between the S(T) and ν(T) dependences, both the Seebeck and Nernst anisotropies evolve very similarly with temperature. Namely, they emerge slightly above the structural transition, then change their character, and eventually sign at the temperature close to the temperature of the pseudog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, such a state can be difficult to identify in materials that have orthorhombic structures, which would naturally couple to any electronic nematic order and vice versa. Despite these challenges, experimental evidence for electronic nematic order that is distinct from the crystal structure include reports of electronic nematicity from bulk transport and magnetometry measurements in YBCO (7)(8)(9)(10), scanning tunneling microscopy (STM) in BSCCO (12,13), inelastic neutron scattering in YBCO (11), Seebeck and Nernst effect in LSCO (23), and resonant x-ray scattering in (La,Nd,Ba,Sr,Eu)2CuO4 (24). Moreover, some studies have hinted at an association between nematicity and the pseudogap phase, with an enhancement of nematicity in the vicinity of the pseudogap onset temperature (10,23) and enhanced electronic nematic fluctuations in the vicinity of the pseudogap QCP (25,26).…”
mentioning
confidence: 99%
“…However, such a state can be difficult to identify in materials that have orthorhombic structures, which would naturally couple to any electronic nematic order and vice versa. Despite these challenges, experimental evidence for electronic nematic order that is distinct from the crystal structure include reports of electronic nematicity from bulk transport and magnetometry measurements in YBCO (7)(8)(9)(10), scanning tunneling microscopy (STM) in BSCCO (12,13), inelastic neutron scattering in YBCO (11), Seebeck and Nernst effect in LSCO (23), and resonant x-ray scattering in (La,Nd,Ba,Sr,Eu)2CuO4 (24). Moreover, some studies have hinted at an association between nematicity and the pseudogap phase, with an enhancement of nematicity in the vicinity of the pseudogap onset temperature (10,23) and enhanced electronic nematic fluctuations in the vicinity of the pseudogap QCP (25,26).…”
mentioning
confidence: 99%
“…More recently, however, some works suggest that the relationship between charge order and superconductivity might be more intimate than simple competition, this means that charge ordered states might be precursor, or enablers, of superconductivity [50,51]. Furthermore, studies in YBa 2 Cu 3 O and LBCO have demonstrated a connection between C4 symmetry broken states and the elusive pseudogap state [52][53][54]. Evidence for a similar situation has been shown in STEM studies of BSCCO [55].…”
Section: Charge and Orbital Orderingmentioning
confidence: 78%